An Investigation Of Differentially Abundant Membrane Proteins In Virulent Versus Avirulent Variants Of Entamoeba Histolytica HM-1:IMSS - Ng, Yee Ling (2018)
Entamoeba histolytica is a protozoan parasite that causes amoebiasis and poses a significant health risk for human populations in the endemic areas. The molecular mechanisms involved in the pathogenesis regulation of the parasite are not well characterized. I-Ience, this study was aimed at identifying and quantifying the differentially abundant membrane proteins by comparing the membrane proteins of virulent and avirulent variants of E. histolytica }-IM-l :IMSS. Additionally, investigation on the potential interactions among the differentially abundant membrane proteins was performed.